Efectos de la discapacidad en la dinámica familiar de los usuarios del centro de fisioterapia y rehabilitación de la oficina municipal de atención a las personas con discapacidad, sub gerencia de derechos humanos de la municipalidad provincial de trujillo, año 2013 - Távara Infante, Edith Tania Tatiana (2014)
The present investigation has studied the effects of the disability in the familiar dynamics of the persons with disability users of the Center of Physical therapy and Rehabilitation of the Municipal Office of Attention to the Persons with Disability of the Sub Gerencia of Human rights of the Provincial Municipality of Trujillo - 2013. For effects of this study the realized investigation, it was of type descriptive - explanatory the same one that allowed to characterize a phenomenon or situation makes concrete of the family indicating his more peculiar features of the familiar dynamics of the users. For it one possessed a sample of 24 users of the Center of Physical therapy and Rehabilitation of the Municipal Office of Attention to the Persons Disability. In agreement to the results obtained in this investigation, to general way was observed that in most of the families of the users, the familiar dynamics met affected with the presence of the disability, provoking a great impact in different levels of the familiar system, where the families must adapt to the new situations that the presence of the disability originates, they must be reorganized, assume new roles, to re-accommodate his structure, to redistribute the tasks depending on the member with disability. Besides in this way of reorganization, difficulties appear in the social environment of the family like it are the creencias and the discrimination, which turns out to be disfunctional for the homeostasis of the familiar system.